The Effect of Good Corporate Governance on Banking Profitability - Gebrill Kimberly Pendong; Yuansi Ester Tumilaar; I Gusti Agung Musa Budidarma (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine and analyze the effect of Good Corporate Governance on profitability in the banking sector listed on the Indonesia Stock Exchange. Proxies of good corporate governance are managerial ownership, institutional ownership, the composition of independent commissioners, and the size of the board of directors, profitability is proxied by the ratio of Return on Net Operating Assets (RNOA). The sample of this research was taken using purposive sampling to obtain 43 companies that meet the criteria as a sample. The data analysis technique in this study used multiple linear regression. The results obtained in this study indicate that managerial ownership, institutional ownership, and the size of the board of directors have no significant effect on profitability, while the composition of independent commissioners has a significant effect on profitability.